Pendampingan Inventarisasi Atraksi, Aksesibilitas, dan Amenitas Desa sebagai Komponen Penilaian Anugerah Desa Wisata (ADWI) Kemenparekraf: Assistance in Inventory of Village Attractions, Accessibility, and Amenity as a Component of the Tourism Village Award (ADWI) Assessment of Kemenparekraf - Saharuna, Muhammad Yusuf; Rahman, Abdu (Politeknik Pariwisata Makassar, 2024)
Tukamasea Village in Maros Regency, South Sulawesi, has significant potential to be developed as a tourist village. However, this potential has not been fully identified and utilized optimally. This community service project aims to provide guidance in the inventory and development of tourist attractions, accessibility, and amenities in Tukamasea Tourist Village. The methods used include field observations, focus group discussions (FGD), and training for the local community. The inventory results show that Tukamasea Village has various potential tourist attractions, such as Dolli Bathing Tourism, Galung Dolli Tourism, Jodoh Hill, and the Red Flower Seed House. Accessibility to the village and between tourist sites is generally good, although some road sections still require improvements. Basic amenities like mosques, schools, and health centers are available, though tourism-supporting facilities still need enhancement. This project also involves empowering the community in tourist village management, including training for Pokdarwis members and local business actors. Development recommendations include improving infrastructure quality, diversifying tourist attractions, strengthening institutions, and implementing more effective promotional strategies. Through this activity, it is hoped that Tukamasea Village can optimize its tourism potential, increase tourist visits, and ultimately boost the local economy. The sustainability of this program needs to be maintained through ongoing collaboration between local government, academics, and the local community.